Memorable Tourism Experiences in Red Tourism: The Case of Jiangxi, China - Zhou, Xuefei; Wong, Jose Weng Chou; Wang, Shan (Anna) (Frontiers in Psychology, 2022)
Red tourism, as a form of special interest tourism (SIT), becomes widespread among Chinese tourists. This study aims to explore MTEs in red tourism destinations and examine how country competence affects intention to visit similar destinations through the influences on MTEs, destination image, red tourism place attachment, and overall satisfaction. The partial least squares structural equation modeling (PLS-SEM) analysis is utilized to analyze the data from 556 tourists. Empirical results reveal that country competence positively influences MTEs and destination image. Furthermore, both MTEs and destination image influence overall satisfaction and red tourism place attachment, but do not influence intention to visit other similar destinations; the relationships between overall satisfaction, intention to visit other similar destinations, and place attachment are all confirmed as well. This study represents one of the few studies that classify red tourism as a form of historical-based special interest tourism, with the purpose of promoting country competence. The outcomes provide a better understanding of both scholars and practitioners of historical-based SIT planning and businesses on how to promote destination image and country competence.